Reconstruction of past variation in lake water balance at upstream Smoky and Wabasca watersheds to improve understanding of causes of lake drying in the Peace-Athabasca Delta - Thibault, Hannah (University of Waterloo, 2023)
Controversy persists regarding causes of recent lake-level drawdown within the internationally recognized Peace-Athabasca Delta (PAD), northern Alberta. Central to this debate are conflicting interpretations of causes of decline in Lower Peace River ice-jam flood frequency that has led to reduced flooding of lakes and water-level drawdown across the delta. On one hand, studies analyzing Peace River hydrometric data and Traditional Knowledge and historical records of ice-jam flood frequency have attributed lake drying to decreased ice-jam flood frequency caused by the W.A.C. Bennett Dam, which has regulated Peace River flow since 1968. Statistical analysis of these records has also been used to establish a hypothesis that ice-jam flood frequency was accelerating prior to construction of the dam and declined thereafter. In contrast, paleolimnological analyses of sediment cores from oxbow and perched lakes in the Peace sector of the PAD identified declining ice-jam flood frequency and lake drying since the late 1800s and attributed this to a shifting climate following the Little Ice Age. Further investigation is needed to delineate influences of climate versus Peace River flow regulation and reconcile contrasting interpretations of the timing and causes of declining ice-jam flood occurrence along the Lower Peace River and lake drying at the PAD. Reconstructing climate-driven hydrological change at the upstream unregulated Smoky and Wabasca watersheds, which provide substantial discharge to the Peace River when ice-jam floods occur at the PAD, may add critical insight into causes of hydrological change at the PAD. Recent analyses of sediment cores from oxbow lakes within the watersheds of these ‘trigger tributaries’ have revealed that flood influence began to decline decades before operation of the W.A.C. Bennett Dam, coincident with decline of ice-jam flood occurrence at the Lower Peace River and lake drying in the PAD (Girard, 2022; Stratton, 2022). Here, paleolimnological analyses of sediment cores from remote, upland lakes in the Smoky and Wabasca watersheds, whose water balance are controlled by climatic variations, are used to build on this newly generated paleohydrological knowledge and reconstruct variation in hydrological conditions from 1880 to 2019. Sediment cores from two upland lakes within each of the Smoky and Wabasca watersheds were used to reconstruct temporal variation in water balance based on evaporation-to-inflow (E/I) ratios computed from cellulose-inferred lake water oxygen isotope records. Relative to the pre-regulation averages (1880–1967), E/I ratios began to rise between ~1910 and 1940 at upland lakes in the Smoky River watershed and ~1960–1970 at upland lakes in the Wabasca River watershed. Use of linear regression for the pre-regulation (1880–1967) and post-regulation (1972–2019) intervals identified statistically significant rises in E/I ratios during the pre-regulation interval at both upland lakes in the Smoky watershed and at one upland lake in the Wabasca watershed, as well as at both upland lakes in the Wabasca watershed during the post-regulation interval. These results reveal that increasing importance of evaporation on water balance, associated with declining snowmelt runoff input, at upland lakes in the unregulated Smoky and Wabasca watersheds began before onset of Peace River flow regulation, and it intensified during the post-regulation interval. Periods of climate-driven increase in importance of evaporation on water balance of the upland lakes coincided with previously obtained paleolimnological evidence of decreasing flood occurrence at floodplain lakes in the Smoky and Wabasca river watersheds, and decreasing flood occurrence at an oxbow lake and increasing evaporation at a perched basin in the Peace sector of the PAD. Correspondence of hydrological change since the 1880s at upland and floodplain lakes located within unregulated and regulated portions of the Peace River watershed identifies a strong role of climate, not regulation of Peace River flow, on the flood regime and lake water balance at the PAD. This knowledge is critical for informing decisions regarding adaptive and mitigative conservation measures at the PAD, including those being contemplated by the federal Wood Buffalo National Park Action Plan.
Keywords: lake water balance; climate; Peace-Athabasca Delta; Smoky and Wabasca watersheds